Banking on research: Who leads? Who follows? Who cares? - Vasconcelos, C.; Damásio, B.; Mendonça, S. (Journal of Institutional Economics, 2025)
This study sheds light on the diffusion of knowledge production as an institutional norm among central, development, and investment banks. It builds on an original database of 24,435 peer-reviewed scientific items published by a pool of 237 central banks, development banks, and investment banks from 1966 to 2023. The focus is on their interactive dynamics, analysed through a two-fold approach: Granger-Causality analysis for linear relationships and a multivariate Markov chain approach for non-linear interactions. Central banks emerge as leaders in scientific production, influencing development and investment banks. Results lead to further questions about inter-institutional agenda-setting, such as how central banks shape research priorities, the extent to which their intellectual leadership impacts others’ priorities, and the mechanisms through which institutional norms are diffused and reinforced within the global financial and policymaking landscape.